Economic Literacy in a Multidimensional Individualistic Perspective: Evidence from Pakistan’s Economy - Waqqas Qayyum, Malik Muhammad (JSSH, 2021)
Analyzing individual behavior has become a central theme in modern day economic literature. Understanding subjective behavior of individuals helps researchers to unfold many important phenomena and critical concepts. This study attempts to explore one such concept “Economic literacy”, which is of practical and theoretical relevance. Economic literacy is among those concepts which on larger part explain the economic subset of individual’s life. The study utilizes survey responses to explore the extent of economic literacy among salaried, self-employed and entrepreneurs and finds considerable heterogeneity among these groups. Economic literacy has been assessed on multidimensional basis whereby the dimensions are characterized by policy awareness, theoretical understanding, institutional awareness and selfaptitude of subjects involved in the survey. Utilizing ordinal levels of economic literacy, the study also offers an empirical investigation of some demographic determinants of this key variable within an ordinal logistic framework. The results reveal that demographics including age, income, education, family background, occupational classification significantly explains differential in ordinal levels of economic literacy. Our study is suggestive of some awareness campaigns and training sessions to be launched to make people more aware about state of the economy, policy making and its covariates.